A discourse analysis of Malaysian and Singaporean final secondary level mathematics textbooks / Mohd Nazriq Noor Ahmad - Mohd Nazriq , Noor Ahmad (2016)
This research is prompted by recent developments in i) Malaysia’s world ranking in Mathematics and Science which has seen it slipping from 10th place to 26th in the 2011 Trends in International Mathematics and Science Study (TIMSS) results, ii) Malaysia’s below average scores in the PISA 2012 tests (the bottom third spot out of 65 countries in Mathematics) and iii) studies showing Malaysian students being demotivated to study subjects that use English as the medium of instruction. Despite its close proximity and shared geo-social history, Singapore on the other hand has maintained very high ranking and standards in mathematics. These issues compel these research questions: How different is Singapore’s mathematics textbook syllabus from Malaysia’s mathematics textbook syllabus in terms of their discourse elements? How do they work together to engage the reader and form the intended understanding of the subject conveyed? In order to compare the discourse patterns found in both Malaysian and Singaporean mathematics textbooks, this research employs various linguistic frameworks proposed by Hyland (2005), Fairclough (2003), Kress & Van Leeuwen (2001), and Scollon & Scollon (2003) to make sense of the data. Preliminary findings and comparisons show that despite having similarities, the students responded differently to the materials presented.